Application and prospects of proteomic technology in inflammation: a review - Senye Wang; Yanhai Chu; Jiajia Yuan; Yiqi Li; Zhenhua Liu; Xiaoyu Chen; Wenyi Kang (Food Science and Human Wellness)
Proteomics is a new technology that has been widely applied in the field of life and health science. It effectively addresses issues related to the impact of dietary structure on organs, tissues, and cells, as well as the changes in proteins in various organs, tissues, and cells under disease conditions. The differential proteins identified through proteomics can serve as disease biomarkers and target proteins affecting health and can be used for disease diagnosis and health regulation. In this paper, the application of proteomics in the field of inflammation in recent years was summarized, especially in the therapeutic target and mechanism of action, which opens up a new way for more effective prevention, diagnosis, and treatment of inflammation, and provides medical protection for human life and health.